PAK Sebagai Agen Perubahan dalam Masyarakat Majemuk: Perspektif Kultural dan Sosial - Yurniman Ndruru; Yurlina Ndruru; Indri Purnama Putri Harefa; Semuel Linggit Topayung (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2024)
This article examines the role of "Pak" as a change agent in a multicultural society from both cultural and social perspectives. In societies characterized by ethnic, cultural, and religious diversity, individuals or groups known as Pak often play a crucial role in facilitating integration and social development. The study explores how Pak functions as a mediator, leader, and driver of social change, addressing the challenges that arise from such diversity. The article focuses on Pak’s involvement in developing inclusive policies, enhancing communication between different groups, and promoting values of tolerance and unity. By analyzing relevant case studies and literature, the article identifies various strategies employed by Pak to improve social well-being and strengthen community cohesion. The findings are intended to provide valuable insights into how change agents like Pak can influence social dynamics in multicultural societies and offer practical recommendations for supporting social integration.